A Comparative Study of Methodologies of Protein Secondary Structure (International Journal of Scientific Research and Management (IJSRM), 2014)
All living organisms are made up of cells and each cell in its turn consists of certain protein consequences which exercise an important role in catalyzing the chemical reactions. So, a study of a protein structure becomes a search lamp in the diagnosis of a disease .when the percent identity between two protein sequences falls below 33%,it necessities to carry out the analysis of protein secondary structure. Of the several methodologies developed to analyze the protein secondary structure, two methods proved to be sound-DSSP(Dictionary of Secondary Structure of Proteins) and GOR(Garnier ,Osguthrope and Robson),Even though the prediction accuracy of GORV is 73.5% due to hazards in its implementation ,GORIV is generally used in spite of its accuracy being only to 64.4%